Emission level of air pollutants during 2019 pre-haze, haze, and post-haze episodes in Kuala Lumpur and Putrajaya / Safari Zainal, Nurfatiha Mursyida Zamre and Md. Firoz Khan - Zainal, Safari; Zamre, Nurfatiha Mursyida; Khan, Md. Firoz (Universiti Teknologi MARA, 2021)
Nowadays, due to population growth and industrialisation, air quality in Malaysia is becoming a critical threat. Air pollution has become a serious issue due to its impacts on humans, animals, and the environment. Malaysia experienced air quality deterioration in 2019 when the episodes of haze happened from July to September. It was due to the local and transboundary sources such as vehicles, factories, power plants, and biomass burning from Sumatra. This study aims to differentiate the level of the potential air pollutants, examine the influence of meteorological factors on the potential air pollutants and determine the local and transboundary impact on the potential air pollutants during episodes of pre-haze, haze, and post-haze in Kuala Lumpur and Putrajaya in 2019. Secondary physical and data on meteorology were obtained from the continuous ambient air quality monitoring (CAQM) stations by the Malaysian Department of Environment (DOE). The data obtained from CAQM were physical: particulate matters (PM2.5 & PM10), carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2), and level ozone (O3); as well as meteorological: temperature (T), relative humidity (RH), wind speed (WS) and wind direction (WDir). Overall, the particulate matter (PM2.5, PM10) and carbon monoxide which are the pollutants that involve the formation of haze in Kuala Lumpur and Putrajaya are higher during haze episodes compared to pre-haze and post-haze episodes while the other pollutants (NO2, SO2, O3) are fluctuated throughout the entire episode due to its sources and the influence of meteorological factors. The backward trajectory indicated that the air pollutants are influenced by wind direction from South West Malaysia (SWM) and North East Malaysia (NEM) throughout the entire year.